Internet for student earnings: working place or communication space - R. Khusainova, Liana (2019)
The article is devoted to the study of new forms of e-business, as in connection with the increasing influence of Internet Commerce, there is a fundamentally new situation in social and labor relations. In recent years, there has been a steady trend of increasing students' interest in earnings in the Network. Students work on the computer, earning money by performing various tasks and projects, which actually led to the development of new forms of employment. The aim of the study is to analyze the practices of copywriting as a form of earnings in the Internet space. The leading method for the study of this problem is the method of free interview, which allows identifying the pros and cons, as well as the subtleties of students’ work on the Internet. The article analyzes the concept of copywriting. Motives of activity in the field of copywriting are described; skills necessary in this type of work are revealed and the basic principles of the copywriter’s successful work are considered. The advantages and disadvantages of copywriting relative to other forms of earnings in the Internet space are established. The novelty and originality of the study lies in the fact that the main socio-psychological qualities necessary for the work of a copywriter are highlighted: literacy; the ability to express thoughts concisely; attentiveness. The main motives of students to earn money on the Internet are established: self-realization in the profession and improvement of their skills; the desire to independently manage their work and free time; the desire to communicate with interesting people. The advantages of copywriting for students are identified: the ability to work remotely and at home, without visiting the office; flexible schedule and the ability to choose the amount of their load; unlimited opportunities for self-development (books, communication on thematic forums); getting pleasure from their work; regulation of their communication circle; self-realization in the profession; the ability to increase their income and its dependence only on the business activity of the copywriter and his/her responsible attitude to business. Disadvantages of copywriting for students are identified: instability (risk of payment’s non-receipt); abnormal working schedule; the need to spend time on activities unrelated to specialization; lack of experience exchange and lack of communication; low wages, which is determined by high competition; the problem of income legalization, as well as the lack of social guarantees, social package, lack of career growth, promotion. The data obtained in the work can be used in labor psychology, age psychology, social psychology, pedagogy, sociology, as well as for further theoretical development of this issue.